An Evaluation of Internal Control System for Fraud Prevention (Case Study at PT Erda Indah) - Ridho, Fahmi; Irianto, Gugus (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research have purpose to evaluate the implementation of internal control system at PT Erda Indah for fraud prevention. The data analysis method which was used is qualitative descriptive analysis with a case study approach. The analysis was performed by describing or depicting factual condition of research object to find out and to analysis fraud problem which was faced by research object. Then an alternative and suggestion were given to solve the problem. The analysis was performed based on standard Committee Of Sponsoring Organization (COSO), control environment, risk assessment, information and communication, control activities, and monitoring analysis. This analysis result showed that the element of control activitiesÂ and monitoring elements still have a weakness in applied, while elements of the control environment, risk assessmentÂ elements, and the elements of informationÂ and communication has been good in applied . Key word: internal control system, fraud, fraud prevention